Hepatitis B Virus and HIV Infection - Martín-Carbonero, Luz; Poveda, Eva (Seminars in Liver Disease, 2012)
Approximately 5 to 10% of human immunodeficiency virus- (HIV-) infected persons worldwide have chronic hepatitis B virus (HBV). The management of these patients merits special attention. They experience a faster progression to cirrhosis and more frequent liver-related death than HBV-monoinfected individuals. For this reason, therapy for both HIV and HBV is a priority in most cases. Some antivirals (i.e., tenofovir, lamivudine, emtricitabine) are active against both viruses and should be part of the antiretroviral treatment choice. However, drugs such as entecavir, telbivudine, or adefovir are active against HBV and may display some residual activity against HIV, occasionally leading to the selection of resistance mutations in the HIV polymerase, as is clearly shown with entecavir. Thus, they should be used only in the context of potent antiretroviral treatment. In this review, the authors will provide updated information on the natural history of HIV/HBV coinfected patients, when and which drugs should be used in treatment, and the concern about selection of drug resistance and vaccine escape mutants.
Keywords: HIV; chronic hepatitis B virus; drug resistance; lamivudine; tenofovir